On the Uses of Keeping a Notebook: Autobiographical Narrative Inquiry and Marion Milner’s A Life of One’s Own - Schultz, Christie (Alberta Journal of Educational Research, 2021)
In 1934, Marion Milner, writing under the pseudonym Joanna Field, published A Life of One’s Own, reflecting on her seven-year undertaking of keeping a diary aimed at answering the question, what makes me happy? The diary itself is not the text of the work. Rather, A Life of One’s Own forms a research text that anticipates contemporary autobiographical narrative inquiry. Recognizing narrative inquiry’s grounding in John Dewey’s 1930s theories of experience, this paper explores the ways in which, first, experience is explicitly valued in the text and, second, the ways in which the text provides evidence that diary or notebook keeping can serve as an important process in autobiographical narrative inquiry. The author concludes the paper by offering reflections on some possible uses of notebook keeping for both narrative inquirers and educators. Key words: autobiographical narrative inquiry; Marion Milner; A Life of One’s Own; notebooks; diaries En 1934, Marion Milner, écrivant sous le pseudonyme de Joanna Field, a publié A Life of One’s Own, une réflexion sur les sept ans pendant lesquels elle a tenu un journal personnel dans le but de répondre à la question Qu’est-ce qui me rend heureuse? Le journal n’est pas le texte de l’œuvre; c’est plutôt A Life of One’s Own qui constitue le texte de recherche et qui préfigure l’enquête narrative autobiographique contemporaine. Reconnaissant le fondement de l’enquête narrative dans les pensées de John Dewey pendant le années 1930 sur l’expérience, cet article explore d’abord les façons dont le texte valorise explicitement l’expérience pour ensuite porter sur les façons dont le texte fournit des preuves que la tenue d’un journal ou d’un carnet peut servir de processus important dans l’enquête narrative autobiographique. L’auteure conclut en offrant des réflexions sur des emplois possibles de la tenue d’un journal, tant pour ceux qui entreprennent une enquête narrative que les éducateurs. Mots clés : Enquête narrative autobiographique; Marion Milner; A Life of One’s Own; carnets; journaux intimes